POTENSI, PREFERENSI DAN PERILAKU MAHASISWA TERHADAP PROFESI AUDITOR - Catur Ragil Sutrisno; Amalia Ilmiani (Fakultas Ekonomi Universitas Pekalongan, 2015)
This study aims to identify and test; potential, preferences and students behavior the auditors profession and thefactors that influence it and to determine the effect of the assumption that an accountant who is not or hasnever been an auditor in KAP is a loser, the preference and behavior. The population of research is all students inAccounting Program of Pekalongan University. Sampling method using purposive sampling and obtained 103samples. Data analysis was performed using the F test, frequency distribution and correlation with regressionmodels Eqution Structural Model (SEM). Based on the F test known students in Accounting Program have adesire to be an auditor and its potential is quite high, though hesitantly. Coefficient path of knowledge andaccess to the behavior of little value, which means the behavior of students towards the auditing profession andaccess to knowledge is not affected but rather influenced the potential benefits which include scienceapplications, challenges, salary, and prestige. Based on the analysis of the F test is known that students whoagree with the assumption accountant that don't or have never been become auditor in KAP is loser tend toaffect the preferences of students to the auditor profession.Keywords: potential, preferences, behavior, professional auditor.